Contemporary immigration psychological perspectives to address challenges and inform solutions - Hendricks, Margaret J.; Moghaddam, Fathali M (American Psychological Association, 2022)
""Gang members, criminals, freeloaders, threats to our country!" "Hard-working, devoted to the family, essential for our country!" In the early decades of the 21st century, sharply divided visions have emerged of immigrants and their role in society, not just in the United States but also in the European Union (EU) and other parts of the world. While solutions to the immigration crisis have been explored by political scientists, economists, and other experts, there is a need for greater contributions from psychologists. The chapters in this book contain psychological reports of the immigration experience globally and highlight solutions provided by psychological science to illustrate how immigrants can add to the economic and cultural strength and dynamism of the host society. This book also critically explores the important themes that characterize the psychology of immigration literature with the goal of further developing the contributions of psychological science to address the challenges and inform solutions to contemporary immigration globally"--